Plant Oils as Potential Sources of Vitamin D - Baur, Anja C.; Brandsch, Corinna; König, Bettina; Hirche, Frank; Stangl, Gabriele I. (Frontiers in Nutrition, 2016)
To combat vitamin D insufficiency in a population, reliable diet sources of vitamin D are required. The recommendations to consume more oily fish and the use of UVB treated yeast are already applied strategies to address vitamin D insufficiency. This study aimed to elucidate the suitability of plant oils as an alternative vitamin D source. Therefore, plant oils that are commonly used in human nutrition were firstly analyzed for their content of vitamin D precursors and metabolites. Secondly, selected oils were exposed to a short-term UVB irradiation to stimulate the synthesis of vitamin D. Finally, to elucidate the efficacy of plant-derived vitamin D to improve the vitamin D status, we fed UVB-exposed wheat germ oil for 4 weeks to mice and compared them with mice that received non-exposed or vitamin D3 supplemented wheat germ oil. Sterol analysis revealed that the selected plant oils contained high amounts of ergosterol, but also 7-dehydrocholesterol (7-DHC), with the highest concentrations found in wheat germ oil. Exposure to UVB irradiation resulted in a partial conversion of ergosterol and 7-DHC to vitamin D2 and D3 in these oils. Mice fed the UVB-exposed wheat germ oil were able to improve their vitamin D status as shown by the rise in the plasma concentration of 25 hydroxyvitamin D (25(OH)D) and the liver content of vitamin D compared to mice fed the non-exposed oil. However, the plasma concentration of 25(OH)D of mice fed the UVB-treated oil did not reach the values observed in the group fed the D3 supplemented oil. It was striking that the intake of the UVB-exposed oil resulted in distinct accumulation of vitamin D2 in the livers of these mice. In conclusion, plant oils, in particular wheat germ oil, contain considerable amounts of vitamin D precursors which can be converted to vitamin D via UVB exposure. However, the UVB-exposed wheat germ oil was less effective to improve the 25(OH)D plasma concentration than a supplementation with vitamin D3.